2015
DOI: 10.1093/jnci/dju505
|View full text |Cite
|
Sign up to set email alerts
|

Role of MYC-Regulated Long Noncoding RNAs in Cell Cycle Regulation and Tumorigenesis

Abstract: Our results provide novel regulatory mechanisms in MYC function through lncRNAs and new potential lncRNA targets of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 27 publications
4
141
0
Order By: Relevance
“…LncRNAs described until now have been shown to be involved in the most diverse cellular processes, such as cell growth and apoptosis, cell pluripotency, and differentiation, through multiple and diverse mechanisms (Bonasio and Shiekhattar, 2014; Fatica and Bozzoni, 2014; Rinn and Chang, 2012). Moreover, our work and that of others has shown that lncRNAs are key regulators of cell transformation and, in some cases, direct transcriptional targets of well-known tumor suppressor and oncogenic factors, such as p53 (Huarte, 2015; Sánchez et al, 2014) and MYC (Hart et al, 2014; Kim et al, 2015). …”
Section: Introductionmentioning
confidence: 51%
“…LncRNAs described until now have been shown to be involved in the most diverse cellular processes, such as cell growth and apoptosis, cell pluripotency, and differentiation, through multiple and diverse mechanisms (Bonasio and Shiekhattar, 2014; Fatica and Bozzoni, 2014; Rinn and Chang, 2012). Moreover, our work and that of others has shown that lncRNAs are key regulators of cell transformation and, in some cases, direct transcriptional targets of well-known tumor suppressor and oncogenic factors, such as p53 (Huarte, 2015; Sánchez et al, 2014) and MYC (Hart et al, 2014; Kim et al, 2015). …”
Section: Introductionmentioning
confidence: 51%
“…Accumulating evidence shows that lncRNAs are involved in physiological and pathological progresses, including embryonic development, organ formation, X chromatin inactivation, tumorigenesis and so on refs 12, 13, 14, 15. LncRNAs can recruit transcription factors and remodelling complexes to modulate gene expression11 and they can also interact with messenger RNAs and regulate the stability of mRNAs.…”
mentioning
confidence: 99%
“…In addition, other lncRNAs can also act as decoys, sequestering intracellular mediators and suppressing their ability to fulfill tumor suppressor functions (10). Recently, several studies have identified clinically relevant lncRNAs in CRC, e.g., serve as prognostic biomarkers (25,30,51,57). To date, a genome-wide transcriptional profiling of the stromal and epithelial colonic coding and noncoding gene signatures in human sigmoid colon and rectal tissue has not been performed.…”
mentioning
confidence: 99%